2004
DOI: 10.1002/jgm.555
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant bispecific antibodies for the targeting of adenoviruses to CEA‐expressing tumour cells: a comparative analysis of bacterially expressed single‐chain diabody and tandem scFv

Abstract: We have generated two distinct recombinant bispecific antibody molecules for the retargeting of adenoviral vectors to CEA-expressing tumour cells. These antibody molecules were produced by combining the antigen-binding sites of a neutralising anti-fibre knob scFv (S11) and an anti-CEA antibody either in a single-chain diabody format (scDb CEA-S11) or a tandem scFv format (taFv CEA-S11). In order to facilitate expression of taFv CEA-S11 in bacteria we selected from a phage display library taFv molecules with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 36 publications
0
24
1
1
Order By: Relevance
“…A previous comparative study of scDb and scFv formats (15), for example, showed that both have similar biological activities in vitro, and these results differ from our results. This difference between results may suggest that the most suitable format of small BsAbs depends on the Fv used and/or their combination, but it seems clear, at least, that converting formats has the potential to increase functionality.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…A previous comparative study of scDb and scFv formats (15), for example, showed that both have similar biological activities in vitro, and these results differ from our results. This difference between results may suggest that the most suitable format of small BsAbs depends on the Fv used and/or their combination, but it seems clear, at least, that converting formats has the potential to increase functionality.…”
Section: Discussioncontrasting
confidence: 99%
“…Hence, refolding techniques or mammalian expression systems are routinely used to produce soluble taFv (25,26). Researchers have engineered linker length (27,28) and optimized linkers using phage display technology (15) to promote the expression of soluble taFv; however, whether these linker sequences are applicable to other taFv is unclear. Additionally, the peptide tag usually required for purification may affect the function of small BsAbs in samples prepared using bacterial or mammalian expression systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main antigens that have been used as targets for bispecific antibodies are overexpressed by tumor cells, including EGFR (Witlox et al, 2002;Reusch et al, 2006), HER2 (Zhu et al, 1996;Maletz et al, 2001a), CD19 (Haagen et al, 1994;Csoka et al, 1996;Chen et al, 1998a, b;Kipriyanov et al, 1998;Loffler et al, 2000b;Manzke et al, 2001a, b;Dreier et al, 2003c), CD20 (Brandl et al, 1999;Xiong et al, 2002;Yu et al, 2005), EpCAM (Maletz et al, 2001b;Wimberger et al, 2003), MUC-1 (Katayose et al, 1996) and CEA (FitzGerald et al, 1997;Holliger et al, 1999;Korn et al, 2004).…”
Section: Bispecific Antibodiesmentioning
confidence: 99%